Revisão taxonômica das espécies de Cis Latreille do grupo tricornis (Coleoptera: Ciidae) - Borlini, Paula Vieira (Universidade Federal de Viçosa, 2025)
Ciidae é uma família de besouros fungívoros diminutos, mundialmente distribuídos. Nesta família há cerca de 780 espécies e 56 gêneros viventes descritos, dos quais 180 espécies e 22 gêneros são Neotropicais. O gênero Cis Latreille, 1797 abarca aproximadamente 360 espécies e quase 40% das espécies neotropicais da família. Parte de suas espécies é organizada em grupos, dos quais os principais representantes neotropicais são dos grupos comptus, pallidus, taurus, tricornis e vitulus. O objetivo geral da tese foi realizar a revisão taxonômica do grupo de espécies Cis tricornis. Os objetivos específicos foram: (i) revisar as espécies de Cis do grupo tricornis e delimitar as características morfológicas do grupo; (ii) redescrever espécies; (iii) designar lectótipos para as espécies Ceracis tricornis Gorham, 1883 e Cis nasicornis Reitter, 1878; (iv) descrever espécies novas para a região Neotropical; (v) fornecer dados de distribuição e de uso de fungo hospedeiro e outras informações pertinentes. Os resultados são apresentados em três capítulos. O primeiro capítulo descreve duas novas espécies do grupo tricornis para a região Neotropical, Cis caipora sp. nov. na Costa Rica e Cis guarani sp. nov. no Brasil. O segundo capítulo define os limites morfológicos, propõe a transferência das espécies do gênero Cis (e desuso do grupo tricornis) e descreve dois gêneros novos, Sacis gen. nov. e Urupecis gen. nov.. Além disso, são designados lectótipos para as espécies Ceracis tricornis e Cis nasicornis. O terceiro capítulo descreve cinco novas espécies brasileiras da região Sul e Sudeste de Mata Atlântica, pertencentes ao gênero Urupecis, sendo elas: U. paradisus sp. nov., U. iris sp. nov., U. caissara sp. nov., U. rufulus sp. nov. e U. euthynus sp. nov., aprimorando conhecimento sobre a fauna Neotropical. Palavras-chave: Ciinae; besouros; Neotropical; taxonomia

Ciidae is a family of minute fungivorous beetles with worldwide distribution. Nearly 780 described species and 56 extant genera have been described, of which 180 species and 22 genera are Neotropical. The genus Cis Latreille, 1797 comprises approximately 360 species, representing almost 40% of the Neotropical Ciidae species. Several Cis species are organized into groups, the main Neotropical representatives belonging to the bilamellatus, comptus, pallidus, taurus, tricornis, and vitulus groups. The general aim of this thesis is to provide a taxonomic review of the Cis tricornis species-group. The specific objectives are to: (i) review the species of Cis tricornis group and delimit morphological features of the group; (ii) redescribe species; (iii) designate lectotypes for Ceracis tricornis Gorham, 1883 and Cis nasicornis Reitter, 1878; (iv) describe new species from the Neotropical region; (v) provide data on geographic distribution, host fungi, and other relevant information. The results are presented in three chapters. The first chapter describes two new species of the tricornis species-group from the Neotropical region, Cis caipora sp. nov. from Costa Rica and Cis guarani sp. nov. from Brazil. The second chapter establishes the morphological limits of the group and proposes transferring species of the Cis tricornis group to two new genera, describing Sacis gen. nov. and Urupecis gen. nov., thereby discontinuing the tricornis group. In addition, lectotypes are designated for Ceracis tricornis and Cis nasicornis. The third chapter describes five new Brazilian species from the Atlantic Forest of the South and Southeast Regions, belonging to Urupecis gen. nov., namely: U. paradisus sp. nov., U. iris sp. nov., U. caissara sp. nov., U. rufulus sp. nov. e U. euthynus sp. nov., thereby contributing to the knowledge of the Neotropical fauna. Keywords: Ciinae; minute-beetles; Neotropical; taxonomy
Taxonomic review of the Cis Latreille species of the tricornis group (Coleoptera: Ciidae)
Keywords: Coleoptera; Ciidae; Cis (Taxonomia); Besouros; Região Neotropical; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES